Meta-cognitive skill training programme for first-year bachelor students using thinking process externalisation environment. (1st January 2013) - Seta, Kazuhisa; Cui, Liang; Ikeda, Mitsuru; Matsuda, Noriyuki; Okamoto, Masahiko
We think that to acquire a skill for co-creating knowledge with others cooperatively, it is important to develop meta-cognitive skill, but to do so is not straightforward. In this paper, we attempt to design a thinking skill (particularly meta-cognitive skill) development curriculum for first-year bachelor-degree students on the basis of the results obtained in two preceding studies that we have performed for postgraduate education and those engaged in medical services. To deal effectively with new learning for first-year bachelor students – 'thinking about thinking' – we designed a curriculum that gives students a knowledge co-creation programme and thinking externalisation tool to devote attention to the thinking process and to have the bodily sensation of its meaning, and we put it into practice. This paper describes a learning model for thinking skill, which is fundamental to appropriate curriculum design, and discusses the design intention of a curriculum conforming to it and the usefulness of the learning programme through examples of using the thinking externalisation tool in practice. Results show that the learning programme developed in this study is useful for cultivating the meta-cognitive skill of bachelor students.